Association of serum MicroRNA-145-5p levels with microvascular complications of type 1 Diabetes: The EURODIAB prospective complications study. (August 2022) - Barutta, Federica; Bellini, Stefania; Guarrera, Simonetta; Matullo, Giuseppe; Schalkwijk, Casper; Stehouwer, Coen D.; Chaturvedi, Nish; Soedamah-Muthu, Sabita S.; Durazzo, Marilena; Gruden, Gabriella
Abstract: Aims: To investigate whether serum miR-145-5p levels were associated with micro-macrovascular chronic complications in patients with type 1 diabetes (DM1). Methods: A nested case-control study from the EURODIAB Prospective Complications Study was performed. Cases ( n = 289) had one or more complications of diabetes, whereas controls ( n = 153) did not have any complication. We measured miR-145-5p levels by qPCR and investigated the association with diabetes complications. Results: Mean miR-145-5p levels were significantly lower in cases with microangiopathy [2.12 (0.86–4.94)] compared to controls [3.15 (1.21–7.36), P < 0.05] even after adjustment for age, gender, and diabetes duration. In logistic regression analysis, miR-145-5p levels in the lowest tertile were associated with an over three-fold increased odds ratio (OR) of albuminuria [3.22 (1.17–8.81)], independently of both demographic and diabetes-related factors. In addition, mir145-5p levels in the lowest tertile were independently and inversely associated with arterial hypertension [1.96 (1.08–3.56)] and hypertension was the mediator of the relationship between miR-145-5p and albuminuria. Conclusions: In this large cohort of DM1 patients, we found an inverse association between miR-145-5p and albuminuria that was mediated by systemic hypertension.